PRO-BEBAYA EFFECTIVENESS AS A LEADING PROGRAM FOR THE GOVERNMENT OF SAMARINDA CITY - Muhammad helmi (Jurnal Riset Inossa, 2022)
Pro-Bebaya is the flagship program of the Mayor of Samarinda in 2022. However, as a pilot project, in 2021, one Neighborhood Association is appointed for each sub-district. Because the program is new, it is necessary to assess the effectiveness of its implementation with a progressive legal approach, namely the operation of law in society. After analyzing several problems. First, the regulations have been revised while the program has not been implemented. Second, the Pro-Bebaya changes/revisions did not have a significant impact. Initially, Pokmas were formed through Urban village meetings, then formed through community meetings. Deliberation in the field is more effective in the Urban village than in the community. Third, in the Pro-Bebaya provisions some assistants assist from the beginning of planning to report, however, during the 2021 Pilot Project, Gunung Panjang Village there was no assistance, and also during the planning and preparation of the RAB proposed by each Neighborhood Association for 2022 they were not accompanied by assistants. Fourth, in 2022 all of the neighborhoods made RAB not check the standard book. Fifth, based on the experience of the Gunung Panjang Pokmas in 2020 and 2021, they experienced difficulties in making reports and taxes. Because reporting does not have standards such as receipts, goods orders (SPB), and Work Received Minutes (BAPPHP), and the tax value is confusing. Sixth, the lack of clarity on the Pro-Bebaya regulations, who will occupy the self-management team among the planning team, implementing team, and supervisory team